Definition, analysis and experimental investigation of operation modes in hydrogen-renewable-based power plants incorporating hybrid energy storage. (1st April 2016) - Valverde, L.; Pino, F.J.; Guerra, J.; Rosa, F.
Highlights: A conceptual analysis of operation modes in energy storage plants is presented. Key Performance Indicators to select operation modes are provided. The approach has been applied to a laboratory hybrid power plant. The methodology provides guidance for the operation of hybrid power plants. Abstract: This paper is concerned with Operating Modes in hybrid renewable energy-based power plants with hydrogen as the intermediate energy storage medium. Six operation modes are defined according to plant topology and the possibility of operating electrolyzer and fuel cell at steady-power or partial load. A methodology for the evaluation of plant performance is presented throughout this paper. The approach includes a set of simulations over a fully validated model, which are run in order to compare the proposed operation modes in various weather conditions. Conclusions are drawn from the simulation stage using a set of Key Performance Indicators defined in this paper. This analysis yields the conclusion that certain modes are more appropriate from technical and practical standpoints when they are implemented in a real plant. From the results of the simulation assessment, selected operating modes are applied to an experimental hydrogen-based pilot plant to illustrate and validate the performance of the proposed operation modes. Experimental results confirmed the simulation study, pointing out the advantages and disadvantages of each operation mode in terms of performance and equipment durability.